Hsp104 Overexpression Cures Saccharomyces cerevisiae [PSI(+)] by Causing Dissolution of the Prion Seeds - Park, Yang-Nim (American Society for Microbiology, 2014)
The [PSI(+)] yeast prion is formed when Sup35 misfolds into amyloid aggregates. [PSI(+)], like other yeast prions, is dependent on the molecular chaperone Hsp104, which severs the prion seeds so that they pass on as the yeast cells divide. Surprisingly, however, overexpression of Hsp104 also cures [PSI(+)]. Several models have been proposed to explain this effect: inhibition of severing, asymmetric segregation of the seeds between mother and daughter cells, and dissolution of the prion seeds. First, we found that neither the kinetics of curing nor the heterogeneity in the distribution of the green fluorescent protein (GFP)-labeled Sup35 foci in partially cured yeast cells is compatible with Hsp104 overexpression curing [PSI(+)] by inhibiting severing. Second, we ruled out the asymmetric segregation model by showing that the extent of curing was essentially the same in mother and daughter cells and that the fluorescent foci did not distribute asymmetrically, but rather, there was marked loss of foci in both mother and daughter cells. These results suggest that Hsp104 overexpression cures [PSI(+)] by dissolution of the prion seeds in a two-step process. First, trimming of the prion seeds by Hsp104 reduces their size, and second, their amyloid core is eliminated, most likely by proteolysis.